2008
DOI: 10.1137/050623012
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Trust-Region Methods for Multiscale Nonlinear Optimization

Abstract: Abstract. A class of trust-region methods is presented for solving unconstrained nonlinear and possibly nonconvex discretized optimization problems, like those arising in systems governed by partial differential equations. The algorithms in this class make use of the discretization level as a mean of speeding up the computation of the step. This use is recursive, leading to true multilevel/multiscale optimization methods reminiscent of multigrid methods in linear algebra and the solution of partial-differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 34 publications
(56 reference statements)
8
173
0
Order By: Relevance
“…Similar bounds have been proved by Gratton, Toint, and co-authors [8,9] for trust-region methods and by Cartis, Gould, and Toint [3] for adaptive cubic overestimation methods, when these algorithms are based on a Cauchy decrease condition. Cartis, Gould, and Toint [4] have shown that such a bound is tight for the steepest descent method by presenting an example where the number of iterations is arbitrarily close to it (these authors have also shown that Newton's method can also take a number of iterations arbitrarily close to O( −2 )).…”
Section: Introductionsupporting
confidence: 56%
“…Similar bounds have been proved by Gratton, Toint, and co-authors [8,9] for trust-region methods and by Cartis, Gould, and Toint [3] for adaptive cubic overestimation methods, when these algorithms are based on a Cauchy decrease condition. Cartis, Gould, and Toint [4] have shown that such a bound is tight for the steepest descent method by presenting an example where the number of iterations is arbitrarily close to it (these authors have also shown that Newton's method can also take a number of iterations arbitrarily close to O( −2 )).…”
Section: Introductionsupporting
confidence: 56%
“…Such a bound has been proved sharp or tight by Cartis, Gould, and Toint [1]. There has been quite an amount of research on WCC bounds for several other classes of algorithms in the non-convex case (see, e.g., [7,9,14]). …”
Section: Introductionmentioning
confidence: 99%
“…The author expects that many of them can be adapted to the more general context discussed here. In particular, one may think of extensions in the spirit of the retrospective trust-region algorithm by Bastin, Malmedy, Mouffe, Toint and Tomanos (2009), or to multilevel frameworks presented by Gratton, Sartenaer and Toint (2008). Which of these will be most useful is a topic for further research.…”
Section: Discussionmentioning
confidence: 99%